SYST-05 OPTIMIZING HER2-TARGETED THERAPIES (TT) FOR BREAST CANCER (BC) LEPTOMENINGEAL METASTASES (LM): A SYSTEMATIC REVIEW AND META-ANALYSIS. (5th August 2022) - Lazaratos, Anna-Maria; Maritan, Sarah; Quaiattini, Andrea; Bouganim, Nathaniel; Dankner, Matthew
Abstract: INTRODUCTION: LM is a debilitating condition associated with metastatic cancers, including BC. When oncogenic drivers are identified, TT represents an appealing therapeutic strategy. However, the efficacy of TT for LM is unknown as LM patients are routinely omitted from clinical trials. METHODS: We conducted a systematic review and meta-analysis of individual patient data to evaluate the effectiveness of HER2-TT in HER2+ BCLM in accordance with PRISMA guidelines. TTs evaluated included trastuzumab (intrathecal (IT) or intravenous (IV)), trastuzumab-emtansine, trastuzumab-deruxtecan, and lapatinib. Primary outcome was overall survival (OS). RESULTS: Of 7780 abstracts screened, 91 publications and a total of 109 patients were included in the final analysis. Patients receiving chemotherapy (either IT, IV, or as part of an antibody-drug conjugate) concurrently with HER2-TT (N=57) exhibited a median OS (mOS) of 44.0 months, compared to patients treated with targeted anti-HER2 therapies alone (N=52), which exhibited a mOS of 14.5 months (P=0.009, hazard ratio (HR): 0.538, 95% confidence interval (CI): 0.328-0.883). Patients receiving IT trastuzumab (N=83) exhibited a median progression-free survival (mPFS) and mOS of 6.0 and 21.0 months, respectively, while patients receiving IV trastuzumab (N=14) exhibited a mPFS and mOS of 6.5 and 27.0 months, respectively (PFS: P=0.31, HR: 0.712, 95% CI: 0.331-1.531; OS: P=0.68, HR: 1.154, 95% CI: 0.587-2.266). In the subgroup of patients receiving IT trastuzumab (N=58), those who concurrently received IT chemotherapy (N=48) exhibited mPFS and mOS of 5.7 and 14.0 months, respectively, while patients concurrently receiving IV chemotherapy (N=10) exhibited a mPFS and mOS of 6.0 and 27.0 months, respectively (PFS: P=0.45, HR: 1.360, 95% CI: 0.602-3.073; OS P=0.29, HR: 1.821, 95% CI: 0.630-5.260). CONCLUSIONS: HER2-TT is an effective therapeutic strategy for BCLM. Patients with BCLM receiving concurrent cytotoxic chemotherapy alongside HER2-TT experience prolonged mOS. IV and IT trastuzumab are similarly effective. Univariate and multivariate analyses will be presented.